2023
DOI: 10.1002/slct.202203946
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Isothermal Kinetics of Phoenix Dactylifera L. Date Palm Seeds Pyrolysis Using Model Fitting and Iso‐Conversional Model Free Methods

Abstract: In this paper, Phoenix dactylifera L. date palm seeds (RDS) were first characterized from a physicochemical point of view, in particular the proximate and ultimate composition, XRD, and SEM-EDX analyses. Based on findings RDS contains 77.4 % of total carbohydrates, 12.8 % of lignin, and a higher heating value (HHV) of 15.88 MJ kg À 1 . Immuno-labeling intensity (OD) of noncellulosic RDS fraction was also determined thanks to the ELISA technique after the dissolution of polysaccharides in ionic liquid showing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Below this transition temperature, the polysaccharides were in a glassy state, characterized by considerable elasticity. These findings align with observations by Marouani et al (2023) , who reported a minor exothermic peak adjacent to the major endothermic dehydration peak, indicative of the decomposition of cellulose within the samples.
Fig.
…”
Section: Resultssupporting
confidence: 92%
“…Below this transition temperature, the polysaccharides were in a glassy state, characterized by considerable elasticity. These findings align with observations by Marouani et al (2023) , who reported a minor exothermic peak adjacent to the major endothermic dehydration peak, indicative of the decomposition of cellulose within the samples.
Fig.
…”
Section: Resultssupporting
confidence: 92%
“…A kinetic analysis based on Coats-Redfern method was performed to determine activation energies and correlations, which includes weight loss curves obtained at a heating rate of 5 °C/min. [48,49] Obtained kinetic parameters are summarized in Table 2.…”
Section: Determination Of the Most Probable Degradation Modementioning
confidence: 99%
“…Criado method based on master curve plots Z(x)/Z(0.5) versus α for different mechanisms was also used to confirm the evolved degradation mechanisms [48,49] for cellulose p-halide benzoates degradation. Obtained plots are illustrated in Figure 7.…”
Section: Determination Of the Most Probable Degradation Modementioning
confidence: 99%